KONSEP MERDEKA SEBAGAI LANDASAN PENDIDIKAN DI ERA KURIKULUM MERDEKA BELAJAR - Lora Devian; Neviyarni; Irda Murni (STKIP Subang, 2023)
Educational philosophy determines educational decisions, alternatives and choices that are guided by education and curriculum developers. The emergence of the term